Ultra Low-Loss Si Substrate for On-Chip UWB GHz Antennas - N. Andre; M. Rack; L. Nyssens; C. Gimeno; D. Oueslati; K. Ben Ali; S. Gilet; C. Craeye; J.-P. Raskin; D. Flandre (IEEE Journal of the Electron Devices Society, 2019)
In this paper, measurements and simulations of miniature monopole antennas for ultra-wideband (UWB) GHz intra- and inter-chips communication and biomedical applications are presented. Folded designs on four substrates are studied: 1) standard bulk; 2) high-resistivity bulk; 3) ultra low-loss radiofrequency silicon-on-insulator (RF SOI); and 4) quartz. Among the Si-based substrates, RF SOI with its trap-rich sublayer demonstrates the best performances with the lowest RF power losses and centimetric transmission distance between antennas. Transmitted power between two antennas was measured from 0.01 to 20 GHz. Using substrate characterization of resistivity, permittivity, and loss tangent based on measured coplanar waveguide lines on the same substrates, good agreement is obtained between the return losses of simulated antennas on each substrate and numerical solutions, confirming the impact of the substrate properties. An antenna bandwidth of 680 MHz is demonstrated at 6.0 GHz meeting the criterion for UWB radio communications in the 6-10 GHz band.